If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -14) = 21 Reorder the terms: (-14 + x) = 21 Remove parenthesis around (-14 + x) -14 + x = 21 Solving -14 + x = 21 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + x = 21 + 14 Combine like terms: -14 + 14 = 0 0 + x = 21 + 14 x = 21 + 14 Combine like terms: 21 + 14 = 35 x = 35 Simplifying x = 35
| 9t-24=57 | | 6x=-4-1 | | 4t-25=9t | | v=.33bh | | w+2=16-6w | | x=120-2x | | x=120-2p | | 4x=3y-7x | | (5x-32)+(3x+28)=180 | | 17/11(5/1)=0 | | 20-2p=3p-10 | | Y=1+1.50x | | 17/11*5/1=7.272727272727272727272727272727272727272727272727272727272727272727272727272727272727272727272727272727727272727272727272727272 | | 17/11*5/1=7.27272727272727272727272727272727272727272727272727273 | | 17/11*5/1=0 | | Y=18-1.25x | | .875a=42 | | x-8.9=-4.6 | | M-5=10 | | 2-[3-(5-x)]=3x-(8+x) | | 8x+1=12x-3 | | 14-2*6+7= | | -8-5x=2+x | | 8x(5+6)=2 | | 15=b+12 | | 6(6x+10)=-3 | | 3y-1=7 | | 4(x-1)=1 | | 7x(11+7)=-2 | | 5w-6=4 | | 4(x-1)+7=8 | | 7-3(y-2)=19 |